Semiconductor SERS enhancement enabled by oxygen incorporation - Zuhui Zheng (Nature Portfolio, 2017)
The application of non-metal-oxide semiconductor materials as surface-enhanced Raman spectroscopy (SERS) substrates is impeded by their low SERS enhancement and detection sensitivity. Here, the authors develop a general oxygen incorporation strategy to magnify these parameters.